A UJI AKTIVITAS ANTIOKSIDAN SEDIAAN LIP BALM EKSTRAK ETANOL DAUN KEJI BELING (Strobilanthes crispus Blume) MENGGUNAKAN METODE DPPH (2,2-difenil-1-pikrihidrazil) - Sinta Nuraesa; Susanti Susanti; Ali Nofriyaldi (Universitas Airlangga, 2024)
Keji beling leaves contained compounds that have the potential to act as moisturizers, namely flavonoids with catechins that function as high antioxidants in preventing free radicals. Keji beling leaf extract can be used as a preparation to overcome dry lips, namely as a moisturizer in the form of lip balm preparations. The purpose of this study was to formulate a lip balm from ethanol extract of keji beling leaves, and to determine the antioxidant activity. This research method included 70% ethanol extract of keji beling leaves with the maceration method and antioxidant activity, namely the DPPH method (2,2-diphenyl-1-picrylhydrazyl) with Vitamin C as a positive control (comparator). The results showed that formula 3 lip balm preparations with 70% ethanol extract of keji beling leaves had antioxidant activity with an IC50 value of 3.12 ppm in the very strong category. Keywords: Antioxidant, Keji Beling Leaves (Strobilanthes crispus Blume), DPPH (2,2-diphenyl-1-picrylhydrazyl), Lip Balm